EVALUATION OF DROUGHT RESISTANCE DURING SEEDS OF TRITICALЕ VARIETIES (Conference Zone, 2022)
In this article, 11 varieties of triticale were evaluated for drought tolerance in the laboratory, and 2 highly resistant varieties were selected and applied to selection work.